Visualization of spherical aberration using an optically levitated droplet as a light source - Marmolejo, Javier Tello; Björnsson, Benjamin; Cabrera-Trujillo, Remigio; Isaksson, Oscar; Hanstorp, Dag (Optics express, 2020)
Optical aberrations can greatly distort the image created by an optical element. Several aberrations can affect the image simultaneously and discerning or visualizing specific aberrations can be difficult. By making use of an optically levitated droplet as a light source, we have visualized the spherical aberration and coma of a lens. The droplet approximates a point source in the ray optic regime but, at the same time, creates a diffraction pattern in the far-field region similar to that used in the Ronchi test. When focused by a lens, this micro double point source creates patterns that resemble comets, barreling, hyperbolic triangles, and, most strikingly, a spider. We show how all these patterns are a consequence of spherical aberration and coma. The Zernike polynomials were used to quantify the value of several individual aberrations by comparing them to patterns resulting from numerical simulations.
Gesehen am 24.11.2020